1971
DOI: 10.1111/j.1600-0609.1971.tb00878.x
|View full text |Cite
|
Sign up to set email alerts
|

An Extra C Chromosome and Various Metabolic Abnormalities in the Bone Marrow from a Patient with Refractory Sideroblastic Anaemia

Abstract: A clinical, cytological and biological study of a 57‐year‐old man with a sideroblastic anaemia is presented. A large population of cells with 47 chromosomes and an extra C chromosome was found in the bone marrow cells but not in skin cells or lymphocytes. The concentration of uracil nucleotides in the bone marrow of the patient was increased. When incubated with 3H‐thymidine the erythroblasts of the patient's marrow showed a low labelling index, A considerable number of early erythroblasts not incorporating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 30 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Similar symptoms have been described in other patients with C trisomy, e.g. Winkelstein et al (1966) and Hellstrom et al (1971). We are raising the question as to whether ineffective erythropoiesis might be related to chromosomal abnormality.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar symptoms have been described in other patients with C trisomy, e.g. Winkelstein et al (1966) and Hellstrom et al (1971). We are raising the question as to whether ineffective erythropoiesis might be related to chromosomal abnormality.…”
Section: Discussionsupporting
confidence: 73%
“…The fact that the extra chromosome was a number 8 in the two cases under discussion does not, of course, imply that all the other cases were also 8-trisomies. Hellstrom et al (1971), however, did briefly mention that they had identified an extra C chromosome as a number 8 in a patient with refractory sideroblastic anaemia. If their case is considered to belong to the same group of malignant haematological diseases as the other patients referred to in this study, then 8-trisomy has been identified in 3 out of perhaps 50 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of pancytopenia, preleukemia and acute leukemia was shown to be associated with chromosomal abnormalities such as trisomy C (Kaur et al 1972). We have found in the literature 14 reported cases of diseases of the hematopoietic system associated with acquired trisomy 8; two patients suffered from sideroblastic anemia (Hellstrom et al 1971, Jonasson et al 1974, two patients showed pancytopenia (de la Chapelle 1972) and another developed acute myeloid leukemia (Jonasson et al 1974). Hsu et al (1974) reviewed an additional five cases with chronic myeloid leukemia and four cases with polycythemia Vera.…”
Section: Discussionmentioning
confidence: 97%
“…[45] Studies have been carried out from time to time to find out the cytogenetics of different types of anemias, and it has been found that not all but many of them are associated with chromosomal changes. There have been reports of aneuploidy[67] and loss of Y chromosome[8] in case of sideroblastic anemias; trisomies of 6 and 8 and loss of chromosome 7[9] in aplastic anemia. Association of reversible cytogenetic abnormalities with megaloblastic anemia have also been observed.…”
Section: Introductionmentioning
confidence: 99%